(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
The presented article is part of an evaluative investigation, in which we propose to determine the value of socio-community practices, promoted at the National University of Río Cuarto since 2009 in all study plans for undergraduate courses. These practices are conceived as learning communities where students, teachers and community actors learn together, participating in a common practice. The interpretive approach used supposes knowing and evaluating, considering the meanings that the actors attribute to these experiences. Particularly in this article we investigate the new ways of learning, the approach to realities that modify subjectivities, the learning of specific competences, the possibilities to rethink the professions and the own emotions from the voices and perspectives of the participants.